Effectiveness of internal audit function as corporate governance mechanism in Tanzanian public sector: The case of Internal Auditor General’s Division - Kimaro, Godlove (2023)
A Dissertation Submitted in Partial Fulfilment of the Requirements for Award of the degree of Master of Science in Accountancy and Finance (MSc A& F) of Mzumbe University